Prevalence of Helicobacter Pylori Infection in Patients with Portal Hypertension - Chaudhary, Shatdal; Rahi, Altaban; Shah, Anita; Shahi, Aakash; Gupta, Badri Kumar; Jaiswal, Niraj Kumar (Journal of Universal College of Medical Sciences, 2018)
Introduction: Helicobacter pylori (H. pylori) is a microaerophile gram-negative bacillus which is found mainly on the surface of mucous membrane of the prepyloric part of the stomach. It is found to be infecting approximately 50% of world population. In patients with liver cirrhosis, the prevalence of H. pylori is variable. A high incidence of H. pylori colonization has been found in portal hypertension; especially in those with gastric erosion. This study was done to find out the prevalence of H. pylori infection in patients with portal hypertension at Universal College of Medical Sciences Teaching Hospital, Nepal. Materials and methods: It was a hospital based cross sectional observational study. All the consecutive patients aged more than 16 years, presented with portal hypertension who fulfilled the inclusion criteria were included in the study. The study period was from 1st September 2015 to 31st August 2016. The upper gastrointestinal endoscopy was done in all cases and mucosal biopsy was taken. H. pylori infection was diagnosed by using rapid urease test. Results: During the study period, 71 patients fulfilled the inclusion criteria and were included in the analysis. The majority of the patients 21 (29.6%) were between 51-60 years age group. There were more male (78.9%) then female (21.1%). The mean age of study population was 50.85 ± 12.47 years. Among the study population, rapid urease test was positive in 70.4% (n=50) patients. Conclusion: The prevalence of H. pylori infection was seen in 70.4% of the patients suffering with portal hypertension.